Coumarin-containing thermoresponsive hyaluronic acid-based nanogels as delivery systems for anticancer chemotherapy. Issue 33 (14th August 2017) - Stefanello, Talitha F.; Couturaud, Benoit; Szarpak-Jankowska, Anna; Fournier, David; Louage, Benoit; Garcia, Francielle P.; Nakamura, Celso V.; De Geest, Bruno G.; Woisel, Patrice; van der Sanden, Boudewijn; Auzély-Velty, Rachel
Abstract : Light- and thermoresponsive hyaluronic acid-based nanogels carry hydrophobic molecules to cancer cells. Abstract : Multi-stimuli responsive nanogels based on biocompatible hydrophilic polymers have emerged as promising drug delivery systems to improve anticancer therapy with hydrophobic drugs, through increase of circulating-time in the bloodstream, tumor-targeting and reduction of systemic toxicity. This paper reports on the synthesis, characterization and biological perspectives of light- and thermoresponsive hyaluronic acid (HA)-based nanogels containing coumarin as the photocleavable group. Newly synthesized nanogels exhibited interesting features: formation by a temperature-triggered self-assembly process, successful incorporation of poorly water-soluble molecules, light-responsiveness as demonstrated by a significant shift in the critical aggregation temperature after light irradiation, efficient internalization by cancer cells overexpressing the CD44 receptor of HA, ability to circulate for a prolonged period of time in the bloodstream after intravenous injection in mice and considerable detection in tumor tissues. Our findings indicate that coumarin-containing HA-based nanogels may be promising delivery systems for anticancer chemotherapy.